Registration of the transition radiation with GaAs detector: Data/MC comparison. (December 2020) - Alozy, J; Belyaev, N; Bergmann, B L; Billoud, T R V; Broulim, P; Burian, P; Campbell, M; Chelkov, G; Cherry, M; Dachs, F; Doronin, S; Filippov, K; et al.
Abstract: New developments of pixel detectors based on GaAs sensors offer effective registration of the transition radiation (TR) X-rays and perform simultaneous measurements of their energies and emission angles. This unique feature opens new possibilities for particle identification on the basis of maximum available information about generated TR photons. Results of studies of TR energy-angular distributions using a 500 |j.m thick GaAs sensor attached to a Timepix3 chip are presented. Measurements, analysis techniques and a comparison with Monte Carlo (MC) simulations are described and discussed.